Determinants Of Family Behavior In Tuberculosis Prevention: A Cross-Sectional Study In Baturraden II Health Center, Indonesia - Nafisah, Lu'lu; Lestari, Widya; Hariyadi, Bambang (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Tuberculosis (TB) remains a major global health challenge until now. Indonesia’s ranking is among the top three high-burden countries. Banyumas Regency reported 3,042 cases in 2021, the highest in Central Java. Families play a critical role in TB prevention, yet their involvement remains suboptimal. This study explores factors influencing family behavior in TB prevention within the Baturraden II Community Health Center area to strengthen prevention strategies.Method: This quantitative study employed a cross-sectional approach. A total sampling technique was used to include all 56 families with TB cases in the Baturraden II Community Health Center working area. Data collection was conducted through interviews using structured questionnaires. Data analysis was done through Chi-Square tests and logistic regressions.Results: The bivariate analysis revealed that knowledge (p=0.001), attitudes (p=0.022), and access to information (p=0.025) were significantly related to TB prevention behavior. The multivariate analysis further indicated that knowledge (p=0.003), attitudes (p=0.010), and access to information (p=0.021) significantly associated to family behavior in preventing tuberculosis. Knowledge emerged as the strongest factor, with an odds ratio (OR) of 10.2, indicating that respondents with low knowledge were 10.2 times more likely to fail in adopting preventive behavior.Conclusion: Family with low knowledge about TB were at a higher risk of not practicing TB prevention in Baturraden II primary healthcare center working area. Enhancing knowledge and promoting appropriate preventive practices are essential strategies for increasing preventive family behavior